2011
DOI: 10.2223/jped.2131
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea associated with <i>Shigella</i> in children and susceptibility of the bacterium to antimicrobials: a study in Teresina, Piau&iacute;, Northeast of Brazil

Abstract: Objective: To evaluate the distribution and susceptibility to antimicrobials of Shigella isolated from children with acute diarrhea and without diarrhea in Teresina, state of Piauí, Brazil. Methods:Four hundred children aged up to 60 months were studied. Stools were collected from all the patients between January 2004 and August 2007. Shigella was identified by conventional methods and antibiogram and extended-spectrum β-lactamase (ESBL) were performed by agar diffusion.Results: Shigellosis was only detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The increase of antimicrobial resistance in Shigella strains has been reported worldwide [6,14,43]. In this work, 116 (89.2%) S. flexneri strains studied were resistant to at least one of the antimicrobials tested (Table 2).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The increase of antimicrobial resistance in Shigella strains has been reported worldwide [6,14,43]. In this work, 116 (89.2%) S. flexneri strains studied were resistant to at least one of the antimicrobials tested (Table 2).…”
Section: Discussionmentioning
confidence: 57%
“…However, we found a low number of strains (1.5%) resistant to nalidixic acid (Table 2). Studies have been shown that resistance to nalidixic acid may lead to reduced susceptibility to fluoroquinolones [6,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the children were affected with parasitic diarrhea, because younger children are exposed to a greater number of environmental factors, such as consuming contaminated food, playing with contaminated soil and consuming contaminated water, than older children. They are immunologically naive, and their delayed humoral immune response makes them more susceptible to infection 4,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus and diarrheagenic Escherichia coli (DEC) are the two most common etiological agents of moderate-to-severe diarrhea in low-income countries (World Health Organization, 2017). Other pathogens such as Cryptosporidium, Shigella, Campylobacter, Salmonella, and Yersinia species also cause human bacterial gastroenteritis, but location-specific etiological patterns also need to be considered (Bottone, 1999;Freitas Neto et al, 2010;Marinou et al, 2012;Nunes et al, 2012;World Health Organization, 2017;Leli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%